Using the Blended Learning to Enhance Students’ Engagement and Learning Experience in Taxation - Setiyani, Rediana; ., Harnanik; Lianingsih, Susmy; Susilowati, Nurdian (KnE Social Sciences, 2020)
This paper examines the student engagement and learning experience in taxation course using blended learning. Blended learning is a combination of face-to-face learning experiences and online learning experiences which aim to complement each other in order to support and enhance student learning. This paper presents the research findings questionnaire surveys of students who currently study taxation courses. The questionnaire was developed and sent to all taxation undergraduate course in Faculty of Economics. Students find that blended learning gives greater flexibility of being able to complete assignments any place and any time. With the adoption of a wide range of delivery methods, blended learning can successfully improve students’ experience and enhance their engagement. It represents an opportunity to integrate the innovative and technological advances offered by online learning with the interaction and participation offered in the best of traditional learning “face to face”. “Face to face interaction” with students is important as students require reassurance and on-going support from lecturers. Providing training for students to use ELENA software in order to equip them to fully utilize blended learning is also essential. Finally, allocation of internet capacity and resources for the development and maintenance of ELENA is also key to its success. Keywords: blended learning, student engagement, learning experience, taxation